Targeting tumor endothelial hyperglycolysis enhances immunotherapy through remodeling tumor microenvironment - Yunlong Shan; Qi Ni; Qixiang Zhang; Mengying Zhang; Bin Wei; Lingge Cheng; Chongjin Zhong; Xinyu Wang; Qingqing Wang; Jiali Liu; Jingwei Zhang; Jingjing Wu; et al. (Elsevier, 2022)
Vascular abnormality is a hallmark of most solid tumors and facilitates immune evasion. Targeting the abnormal metabolism of tumor endothelial cells (TECs) may provide an opportunity to improve the outcome of immunotherapy. Here, in comparison to vascular endothelial cells from adjacent peritumoral tissues in patients with colorectal cancer (CRC), TECs presented enhanced glycolysis with higher glyceraldehyde-3-phosphate dehydrogenase (GAPDH) expression. Then an unbiased screening identified that osimertinib could modify the GAPDH and thus inhibit its activity in TECs. Low-dose osimertinib treatment caused tumor regression with vascular normalization and increased infiltration of immune effector cells in tumor, which was due to the reduced secretion of lactate from TECs by osimertinib through the inhibition of GAPDH. Moreover, osimertinib and anti-PD-1 blockade synergistically retarded tumor growth. This study provides a potential strategy to enhance immunotherapy by targeting the abnormal metabolism of TECs.